2022
DOI: 10.1007/s10872-022-00642-9
|View full text |Cite
|
Sign up to set email alerts
|

Use of AERONET-OC for validation of SGLI/GCOM-C products in Ariake Sea, Japan

Abstract: A station of AErosol RObotic NETwork Ocean Color (AERONET-OC) has been set on the Ariake Observation Tower of Saga University on April, 2018, for verification of the Second generation Global Imager (SGLI)/Global Change Observation Mission-Climate (GCOM-C). Remote sensing reflectance (Rrs) observed by the AERONET-OC was used for verification of SGLI. SGLI Version 1 data underestimated the shortwave Rrs and Rrs (380) and Rrs(412) were mostly negative, while the estimation was improved by Version 2 with the corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…When this is combined with taking hyperspectral measurements and integrating over the satellite spectral response function, the data from a single site can be used to reconstruct the signal for many optical missions (S2, S3, PROBA-V, MODIS, VIIRS, L8, Pléiades, ENMAP, PRISMA, SABIAMAR, PACE, etc.). The existing AERONET-OC (Zibordi et al, 2009;Zibordi et al, 2021) and RadCalNet (Bouvet et al, 2019) networks provide reference in situ measurements, and have been shown to be suitable for performing validation of satellite products (e.g., Alonso et al, 2019;Ishizaka et al, 2022;Zibordi et al, 2022). However both these networks are based on multispectral instruments (with the exception of the Chinese RadCalNet sites), which require spectral interpolation and modelling associated uncertainties to cover all spectral bands of all sensors.…”
Section: Introductionmentioning
confidence: 99%
“…When this is combined with taking hyperspectral measurements and integrating over the satellite spectral response function, the data from a single site can be used to reconstruct the signal for many optical missions (S2, S3, PROBA-V, MODIS, VIIRS, L8, Pléiades, ENMAP, PRISMA, SABIAMAR, PACE, etc.). The existing AERONET-OC (Zibordi et al, 2009;Zibordi et al, 2021) and RadCalNet (Bouvet et al, 2019) networks provide reference in situ measurements, and have been shown to be suitable for performing validation of satellite products (e.g., Alonso et al, 2019;Ishizaka et al, 2022;Zibordi et al, 2022). However both these networks are based on multispectral instruments (with the exception of the Chinese RadCalNet sites), which require spectral interpolation and modelling associated uncertainties to cover all spectral bands of all sensors.…”
Section: Introductionmentioning
confidence: 99%